Thermoplastic resin composition and part, and method for producing part made of thermoplastic resin composition and method for improving mechanical strength
By adding a small amount of carbon nanostructure to thermoplastic resin compositions, the mechanical strength and properties of the resin are enhanced without degrading tensile elongation or impact resistance, addressing the limitations of traditional filler methods.
Patent Information
- Application Number
- JP2020119063
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-07-10
AI Technical Summary
When fillers are added to thermoplastic resins to improve mechanical strength and elastic modulus, it often results in a decrease in tensile elongation at break and impact resistance.
Incorporating a small amount of carbon nanostructure into the thermoplastic resin composition during melt kneading, specifically between 0.1 to 0.5 parts by mass per 100 parts by mass of resin, to enhance mechanical properties without compromising tensile elongation or impact resistance.
The addition of carbon nanostructure effectively improves mechanical strength, tensile strength, and bending modulus of the thermoplastic resin composition while maintaining or minimizing reductions in tensile elongation at break and impact resistance.
Smart Images

Figure 0007658726000001 
Figure 0007658726000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composition and a member molded therefrom, as well as a method for producing a member made of a thermoplastic resin composition and a method for improving the mechanical strength of the member. [Background technology]
[0002] Thermoplastic resins such as polyacetal resin, polyarylene sulfide resin, polybutylene terephthalate resin, polyethylene terephthalate resin, and polyamide resin are used in many fields as engineering plastics due to their excellent physical and mechanical properties, chemical resistance, etc. In thermoplastic resins, various additives are generally added for the purpose of improving performance such as mechanical properties (see Patent Document 1). Examples of such additives include various fillers such as fibrous fillers such as glass fibers, plate-like fillers such as glass flakes and talc, and spherical fillers such as glass beads. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-144002 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, when adding such fillers to improve mechanical strength and elastic modulus, it is necessary to add a certain amount of filler to the thermoplastic resin, which reduces the tensile elongation at break and impact resistance.
[0005] The present invention has been made in consideration of the above-mentioned problems in the conventional art, and an object of the present invention is to provide a thermoplastic resin composition and a part that can improve mechanical properties without significantly impairing tensile elongation at break or impact resistance, as well as a method for producing a part made of a thermoplastic resin composition and a method for improving mechanical strength. [Means for solving the problem]
[0006] The present invention was made based on the discovery that it is possible to improve mechanical strength without significantly impairing tensile elongation at break or impact resistance by simply adding a small amount of carbon nanostructure to a thermoplastic resin. One aspect of the present invention that solves the above problems is as follows. (1) A thermoplastic resin composition obtained by melt-kneading at least 0.1 to 0.5 parts by mass of a carbon nanostructure with respect to 100 parts by mass of a thermoplastic resin.
[0007] (2) The thermoplastic resin composition according to (1) above, wherein the thermoplastic resin is one selected from the group consisting of polyacetal resin, polyarylene sulfide resin, polybutylene terephthalate resin, polyethylene terephthalate resin, and polyamide resin.
[0008] (3) A member obtained by molding the thermoplastic resin composition according to (1) or (2) above.
[0009] (4) preparing a thermoplastic resin composition by melt-kneading at least 0.1 to 0.5 parts by mass of a carbon nanostructure with respect to 100 parts by mass of a thermoplastic resin; and A method for producing a member, comprising: a step of molding the thermoplastic resin composition into a predetermined shape.
[0010] (5) A method for improving the mechanical strength of a member made of a thermoplastic resin composition, comprising using a resin composition obtained by melt-kneading 0.1 to 0.5 parts by mass of a carbon nanostructure to 100 parts by mass of a thermoplastic resin. Effect of the Invention
[0011] According to the present invention, it is possible to provide a thermoplastic resin composition and a part that can improve mechanical properties without significantly impairing tensile elongation at break or impact resistance, as well as a method for producing a part made of a thermoplastic resin composition and a method for improving mechanical strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <Thermoplastic resin composition> The thermoplastic resin composition of this embodiment is characterized in that it is obtained by melt-kneading at least 0.1 to 0.5 parts by mass of carbon nanostructure (hereinafter also referred to as "CNS") with respect to 100 parts by mass of a thermoplastic resin. Hereinafter, each component of the thermoplastic resin composition of the present embodiment will be described.
[0013] [Thermoplastic resin] In this embodiment, the thermoplastic resin may be a crystalline thermoplastic resin, such as polyacetal resin (hereinafter also referred to as "POM resin"), polyarylene sulfide resin (hereinafter also referred to as "PAS resin"), polybutylene terephthalate resin (hereinafter also referred to as "PBT resin"), polyethylene terephthalate resin, polyamide resin, etc. Among them, the thermoplastic resin is preferably one selected from the group consisting of polyacetal resin, polyarylene sulfide resin, polybutylene terephthalate resin, polyethylene terephthalate resin, and polyamide resin. Below, POM resin, PAS resin, and PBT resin are given as examples of the thermoplastic resin, but the present embodiment is not limited thereto.
[0014] (Polyacetal resin (POM resin)) POM resin is a polymeric compound having an oxymethylene group (-CHO-) as a main constituent unit, and may be either a polyacetal homopolymer or a polyacetal copolymer. A polyacetal copolymer has an oxymethylene group as a main repeating unit, and contains other constituent units such as a small amount of comonomer units such as ethylene oxide, 1,3-dioxolane, and 1,4-butanediol formal. Other polymers include terpolymers and block polymers, and either of these may be used. POM resin may have not only linear molecules but also branched or crosslinked structures, and may be a known modified polyacetal resin into which other organic groups have been introduced. POM resin is not particularly limited with respect to its degree of polymerization, and may be any resin that has melt moldability (for example, a melt flow rate (MFR) of 1.0 g / 10 min or more and 100 g / 10 min or less measured at 190°C and a load of 2160 g according to ISO1133). The POM resin is produced by a known production method.
[0015] (Polybutylene terephthalate resin (PBT resin)) PBT resin is a resin obtained by polycondensation of a dicarboxylic acid component containing at least terephthalic acid or its ester-forming derivative (C1-6 alkyl ester, acid halide, etc.) and a glycol component containing at least alkylene glycol having 4 carbon atoms (1,4-butanediol) or its ester-forming derivative (acetylated product, etc.). The PBT resin is not limited to homopolybutylene terephthalate, but may be a copolymer containing 60 mol % or more (particularly 75 mol % or more and 95 mol % or less) of butylene terephthalate units.
[0016] The amount of terminal carboxyl groups in the PBT resin is not particularly limited as long as it does not impair the effects of the thermoplastic resin of this embodiment. The amount of terminal carboxyl groups in the PBT resin is preferably 30 meq / kg or less, and more preferably 25 meq / kg or less.
[0017] The intrinsic viscosity (IV) of the PBT resin is preferably 0.65 to 1.20 dL / g. When a PBT resin having an intrinsic viscosity in this range is used, the resulting resin composition has excellent mechanical properties and flowability. Conversely, if the intrinsic viscosity is less than 0.65 dL / g, excellent mechanical properties cannot be obtained, and if it exceeds 1.20 dL / g, excellent flowability may not be obtained. In addition, the intrinsic viscosity of the PBT resin having the above range can be adjusted by blending PBT resins having different intrinsic viscosities. For example, a PBT resin having an intrinsic viscosity of 0.8 dL / g can be prepared by blending a PBT resin having an intrinsic viscosity of 0.9 dL / g with a PBT resin having an intrinsic viscosity of 0.7 dL / g. The intrinsic viscosity (IV) of the PBT resin can be measured, for example, in o-chlorophenol at a temperature of 35°C.
[0018] In the PBT resin, examples of dicarboxylic acid components (comonomer components) other than terephthalic acid and its ester-forming derivatives include C8-14 aromatic dicarboxylic acids such as isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-dicarboxydiphenyl ether; C4-16 alkanedicarboxylic acids such as succinic acid, adipic acid, azelaic acid, and sebacic acid; C5-10 cycloalkanedicarboxylic acids such as cyclohexanedicarboxylic acid; and ester-forming derivatives of these dicarboxylic acid components (C1-6 alkyl ester derivatives, acid halides, etc.). These dicarboxylic acid components can be used alone or in combination of two or more.
[0019] Among these dicarboxylic acid components, C8-12 aromatic dicarboxylic acids such as isophthalic acid, and C6-12 alkanedicarboxylic acids such as adipic acid, azelaic acid, and sebacic acid are more preferred.
[0020] In the PBT resin, examples of glycol components (comonomer components) other than 1,4-butanediol include C2-10 alkylene glycols such as ethylene glycol, propylene glycol, trimethylene glycol, 1,3-butylene glycol, hexamethylene glycol, neopentyl glycol, and 1,3-octanediol; polyoxyalkylene glycols such as diethylene glycol, triethylene glycol, and dipropylene glycol; alicyclic diols such as cyclohexanedimethanol and hydrogenated bisphenol A; aromatic diols such as bisphenol A and 4,4'-dihydroxybiphenyl; C2-4 alkylene oxide adducts of bisphenol A, such as 2-mol ethylene oxide adducts of bisphenol A and 3-mol propylene oxide adducts of bisphenol A; and ester-forming derivatives of these glycols (acetylated products, etc.). These glycol components can be used alone or in combination of two or more.
[0021] Among these glycol components, C2-6 alkylene glycols such as ethylene glycol and trimethylene glycol, polyoxyalkylene glycols such as diethylene glycol, and alicyclic diols such as cyclohexanedimethanol are more preferred.
[0022] Examples of comonomer components that can be used in addition to the dicarboxylic acid component and the glycol component include aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 4-carboxy-4'-hydroxybiphenyl, etc.; aliphatic hydroxycarboxylic acids such as glycolic acid and hydroxycaproic acid; C3-12 lactones such as propiolactone, butyrolactone, valerolactone, caprolactone (ε-caprolactone, etc.); and ester-forming derivatives of these comonomer components (C1-6 alkyl ester derivatives, acid halides, acetylated products, etc.).
[0023] (Polyarylene sulfide resin (PAS resin)) PAS resin is characterized by its excellent mechanical properties, electrical properties, heat resistance and other physical and chemical properties, as well as its good processability. PAS resin is a polymeric compound mainly composed of a repeating unit -(Ar-S)- (where Ar is an arylene group), and in this embodiment, a PAS resin with a generally known molecular structure can be used.
[0024] Examples of the arylene group include p-phenylene, m-phenylene, o-phenylene, substituted phenylene, p,p'-diphenylenesulfone, p,p'-biphenylene, p,p'-diphenyleneether, p,p'-diphenylenecarbonyl, naphthalene, etc. The PAS resin may be a homopolymer consisting of the above repeating units, or a copolymer containing the following different repeating units may be preferred from the standpoint of processability, etc.
[0025] As the homopolymer, a polyphenylene sulfide resin (hereinafter also referred to as "PPS resin") using p-phenylene group as the arylene group and having p-phenylene sulfide group as a repeating unit is preferably used. As the copolymer, a combination of two or more different arylene sulfide groups consisting of the above-mentioned arylene groups can be used, and a combination containing p-phenylene sulfide group and m-phenylene sulfide group is particularly preferably used. Among them, a combination containing 70 mol % or more, preferably 80 mol % or more of p-phenylene sulfide group is suitable from the viewpoint of physical properties such as heat resistance, moldability, and mechanical properties. Among these PAS resins, a high molecular weight polymer having a substantially linear structure obtained by condensation polymerization from a monomer mainly composed of a bifunctional halogenated aromatic compound can be particularly preferably used. The PAS resin used in this embodiment may be a mixture of PAS resins having two or more different molecular weights.
[0026] In addition to the linear PAS resin, examples of the polymer include a polymer in which a partially branched or crosslinked structure is formed by using a small amount of a monomer such as a polyhaloaromatic compound having three or more halogen substituents during condensation polymerization, and a polymer in which the melt viscosity is increased by oxidative crosslinking or thermal crosslinking by heating a low molecular weight linear polymer at high temperature in the presence of oxygen or the like, thereby improving moldability.
[0027] The melt viscosity of the PAS resin used as the base resin in this embodiment (310°C, shear rate 1200 sec -1 ) is preferably 5 to 500 Pa·s, including the above mixed system.
[0028] [Carbon Nanostructure (CNS)" In the thermoplastic resin composition of this embodiment, a predetermined amount of CNS is added to the thermoplastic resin, and the mechanical properties are improved by the nucleating agent effect of the CNS. More specifically, it is considered that by adding a predetermined amount of CNS to the thermoplastic resin, the CNS functions as a nucleating agent, and the mechanical properties can be improved by the nucleating agent effect. Moreover, since the nucleating agent effect is exerted by a small amount of CNS, the mechanical strength can be improved by the above-mentioned small amount of CNS. In this embodiment, the "nucleating agent" is synonymous with "crystal nucleating agent", "nucleating agent", etc.
[0029] The CNS used in this embodiment is a structure containing multiple carbon nanotubes bonded together, and the carbon nanotubes are bonded to other carbon nanotubes through branched bonds or cross-linked structures. Details of such CNS are described in U.S. Patent Application Publication No. 2013-0071565, U.S. Patent Nos. 9,113,031, 9,447,259, and 9,111,658.
[0030] The CNS used in this embodiment may be a commercially available product, such as ATHLOS 200 or ATHLOS 100 manufactured by CABOT.
[0031] In the thermoplastic resin composition of the present embodiment, the method for adding CNS to the thermoplastic resin is not particularly limited, and can be carried out by a conventionally known method.
[0032] In the thermoplastic resin composition of the present embodiment, the CNS is contained in an amount of 0.1 to 0.5 parts by mass relative to 100 parts by mass of the thermoplastic resin. If the CNS content is less than 0.1 parts by mass, the mechanical strength is poor, and if it exceeds 0.5 parts by mass, the tensile elongation at break is significantly reduced. The CNS content is preferably 0.1 to 0.4 parts by mass, and more preferably 0.1 to 0.3 parts by mass.
[0033] In the present embodiment, a nucleating agent may be used in combination as long as it does not impair the effect of the nucleating agent. Examples of the nucleating agent include carbon black, calcium carbonate, mica, talc, kaolin, titanium oxide, alumina, calcium silicate, boron nitride, and ammonium chloride.
[0034] [Other ingredients] The thermoplastic resin composition of the present embodiment may contain various stabilizers selected as necessary. Examples of the stabilizers used here include one or more of hindered phenol compounds, nitrogen-containing compounds, hydroxides of alkali or alkaline earth metals, inorganic salts, carboxylates, etc. Furthermore, as long as the above-mentioned effects are not inhibited, one or more of general additives for thermoplastic resins, such as colorants such as dyes and pigments, lubricants, release agents, antistatic agents, surfactants, flame retardants, or organic polymer materials, inorganic or organic fibrous, powdery, or plate-like fillers, etc., may be added as necessary.
[0035] The method for producing a molded article using the thermoplastic resin composition of the present embodiment is not particularly limited, and a known method can be adopted. For example, the thermoplastic resin composition of the present embodiment can be fed into an extruder, melt-kneaded and pelletized, and the pellets can be fed into an injection molding machine equipped with a predetermined mold and injection molded to produce a molded article.
[0036] <Materials> The member of the present embodiment is formed by molding the above-mentioned thermoplastic resin composition of the present embodiment, and therefore has high mechanical strength, similar to the thermoplastic resin composition of the present embodiment.
[0037] The member of the present embodiment can be widely used in applications where a thermoplastic resin composition is used. For example, it can be suitably used in automobile parts such as fuel pipe parts and electric / electronic parts such as printer parts, but it is merely an example and is not limited thereto.
[0038] <Method of manufacturing components> The manufacturing method of the component of this embodiment is characterized by including a step of preparing a thermoplastic resin composition obtained by melt-kneading at least 0.1 to 0.5 parts by mass of carbon nanostructure per 100 parts by mass of thermoplastic resin (hereinafter referred to as "Step A"), and a step of molding the thermoplastic resin composition into a predetermined shape (hereinafter referred to as "Step B"). Each step will be described below.
[0039] [Process A] In step A, a thermoplastic resin composition is prepared by melt-kneading at least 0.1 to 0.5 parts by mass of carbon nanostructure with respect to 100 parts by mass of thermoplastic resin. The preferred components in the thermoplastic resin composition, their preferred contents, and other components are as described above. The thermoplastic resin composition is obtained by melt-kneading the above components and, if necessary, other components according to a standard method. For example, the thermoplastic resin composition of the present embodiment can be obtained by feeding the thermoplastic resin composition of the present embodiment into an extruder, melt-kneading the mixture, and pelletizing the mixture. The CNS may be prepared as a master batch in advance, and this master batch may be used when adding the CNS. The master batch refers to a thermoplastic resin composition containing a high concentration of CNS that is prepared in advance.
[0040] [Process B] In step B, the thermoplastic resin composition is molded into a predetermined shape. For example, the pellets obtained as described above are placed in an injection molding machine equipped with a predetermined mold and injection molded.
[0041] As described above, the manufacturing method of this embodiment makes it possible to manufacture a member having sufficient mechanical strength.
[0042] <Method for improving mechanical strength of member made of thermoplastic resin composition> The method for improving the mechanical strength of a member made of a thermoplastic resin composition of this embodiment is characterized by using a resin composition obtained by melt-kneading 0.1 to 0.5 parts by mass of carbon nanostructure per 100 parts by mass of thermoplastic resin. As described above, the thermoplastic resin composition of the present embodiment exhibits a nucleating agent effect by adding a predetermined amount of CNS, and the mechanical strength can be improved. In other words, by using the thermoplastic resin composition of the present embodiment as a member, the mechanical strength of the member can be improved. In the method for improving the mechanical strength of a member made of the thermoplastic resin composition of the present embodiment, the preferred thermoplastic resin, CNS content, and other components are as described above for the thermoplastic resin composition of the present embodiment. EXAMPLES
[0043] The present embodiment will be described in more detail below with reference to examples, but the present embodiment is not limited to the following examples.
[0044] [Examples 1 to 5, Comparative Examples 1 to 8] In each of the Examples and Comparative Examples, the raw material components (except glass fiber) shown in Tables 1 and 2 were dry blended, then fed into a twin-screw extruder (glass fiber was added by side feed), melt-kneaded, and pelletized. The cylinder temperatures of the twin-screw extruder were 200°C for POM resin, 320°C for PPS resin, and 260°C for PBT resin. In Tables 1 and 2, the numerical values of each component indicate parts by mass. The details of each raw material component used are shown below. (1)Thermoplastic resin Polyacetal resin Polyacetal resin: Polyacetal copolymer obtained by copolymerizing 96.7% by mass of trioxane and 3.3% by mass of 1,3-dioxolane (Melt flow rate (MFR) (measured in accordance with ISO1133 at 190°C and a load of 2160 g): 9.0 g / 10 min) Polyphenylene sulfide resin Fortron KPS (melt viscosity: 130 Pa·s (shear rate: 1200 sec) manufactured by Kureha Corporation -1 , 310℃) (Melt viscosity measurement of PPS resin) The melt viscosity of the PPS resin was measured as follows. A capillograph manufactured by Toyo Seiki Seisakusho Co., Ltd. was used, and a flat die with a diameter of 1 mm and a length of 20 mm was used as the capillary. The barrel temperature was 310°C and the shear rate was 1200 sec. -1 The melt viscosity at 100° C. was measured. Polybutylene terephthalate resin Polybutylene terephthalate resin manufactured by Polyplastics Co., Ltd. (intrinsic viscosity (measured in o-chlorophenol at 35°C): 1.0 dL / g)
[0045] (2) Carbon Nanostructure (CNS) CABOT, ATHLOS 200 (3) Nucleating agent Boron nitride Denka Boron Nitride GP, manufactured by Denka Co., Ltd.
[0046] (4) Filler ·talc Crown Talc PP, manufactured by Matsumura Sangyo Co., Ltd. Glass beads Potters Barotini Co., Ltd., EGB731 Glass fiber 1 Nippon Electric Glass Co., Ltd., ECS03T-651G Glass fiber 2 Chopped strands, manufactured by Owens Corning Japan LLC Fiber diameter: 10.5 μm, length: 3 mm
[0047] [Table 1]
[0048] [Table 2]
[0049] [evaluation] Multipurpose test pieces and rectangular test pieces as specified in ISO294-1 were molded by injection molding under the following conditions and used for the following evaluations. ·POM resin composition Molding machine: Toshiba Machine Co., Ltd. EC40 Molding was carried out in accordance with ISO9988-1,2. ·PBT resin composition Molding machine: Toshiba Machine Co., Ltd. EC40 Cylinder temperature: 260℃ Mold temperature: 80℃ ·PPS resin composition Forming machine: Japan Steel Works, Ltd., Nikko J55AD-60H-USM Cylinder temperature: 320℃ Mold temperature: 150℃
[0050] (1) Tensile strength The test pieces obtained as described above were used to measure the tensile strength in accordance with ISO 527-1 and 2. The measurement results are shown in Tables 1 and 2.
[0051] (2) Tensile elongation at break The test pieces obtained as described above were used to measure the tensile elongation at break in accordance with ISO 527-1, 2. The measurement results are shown in Tables 1 and 2.
[0052] (3) Flexural modulus The test pieces thus obtained were used to measure the flexural modulus in accordance with ISO 179. The measurement results are shown in Tables 1 and 2.
[0053] (4) Impact resistance (Charpy impact strength) The test pieces thus obtained were used to measure the Charpy impact strength (notched) in accordance with ISO179 / 1eA. The measurement results are shown in Tables 1 and 2.
[0054] From Table 1, it can be seen that in Examples 1 to 5, all the evaluations were good. That is, in Examples 1 to 5, it was possible to improve the mechanical properties without significantly impairing the tensile breaking elongation or impact resistance. More specifically, it is as follows. That is, when Examples 1 to 3 using POM resin are compared with Comparative Examples 1 to 5, Comparative Example 1 not containing CNS was inferior to Examples 1 to 3 in tensile strength and flexural modulus. Also, Comparative Example 2 in which the content of CNS is 1 part by mass per 100 parts by mass of thermoplastic resin was inferior to Examples 1 to 3 in tensile breaking elongation. In particular, Comparative Example 2 has a more significant decrease in tensile breaking elongation compared to Examples 1 to 3 than Comparative Example 1 not containing CNS. On the other hand, Comparative Examples 3 to 5 in which no CNS was contained and a general filler was added were inferior in impact resistance. Comparing Example 4, which uses a PPS resin, with Comparative Example 6, it is found that Example 4 has improved tensile strength and flexural modulus without any substantial decrease in tensile breaking elongation. Comparing Example 5, which uses a PBT resin, with Comparative Example 7, which does not contain CNS, Example 5 has improved tensile strength and flexural modulus without reducing impact resistance. Similarly, comparing Example 5 with Comparative Example 8, which uses a nucleating agent, Comparative Example 8 is inferior to Example 5 in impact resistance.
Claims
1. The thermoplastic resin is melt-kneaded with at least 0.1 to 0.5 parts by mass of a carbon nanostructure relative to 100 parts by mass of the thermoplastic resin. the thermoplastic resin is one selected from the group consisting of polyacetal resin, polyarylene sulfide resin, polybutylene terephthalate resin, polyethylene terephthalate resin, and polyamide resin; The carbon nanostructure after melt-kneading is a structure containing a plurality of carbon nanotubes bonded to each other, and the carbon nanotubes are bonded to other carbon nanotubes through branched bonds or crosslinked structures (excluding those in which the crosslinked structures are granular portions).
2. A member obtained by molding the thermoplastic resin composition according to claim 1.
3. A step of preparing a thermoplastic resin composition obtained by melt-kneading at least 0.1 to 0.5 parts by mass of a carbon nanostructure with respect to 100 parts by mass of a thermoplastic resin; and The method includes a step of molding the thermoplastic resin composition into a predetermined shape, the thermoplastic resin is one selected from the group consisting of polyacetal resin, polyarylene sulfide resin, polybutylene terephthalate resin, polyethylene terephthalate resin, and polyamide resin; A method for manufacturing a component, in which the carbon nanostructure after melt-kneading is a structure containing multiple carbon nanotubes in a bonded state, and the carbon nanotubes are bonded to other carbon nanotubes by branched bonds or cross-linked structures (excluding those in which the cross-linked structures are granular portions).
4. A method for improving the mechanical strength of a member made of a thermoplastic resin composition, using a resin composition obtained by melt-kneading 0.1 to 0.5 parts by mass of a carbon nanostructure with respect to 100 parts by mass of a thermoplastic resin, the carbon nanostructure after melt-kneading being a structure containing a plurality of carbon nanotubes in a bonded state, the carbon nanotubes being bonded to other carbon nanotubes through a branched bond or a cross-linked structure (however, excluding those in which the cross-linked structure is a granular portion).
Citation Information
Patent Citations
Reinforced conductive polymer
JP1996508534A
Thermoplastic elastomer composition
JP2007112885A
Composite material
JP2007119647A
Polyarylene sulfide composition
JP2008144002A
Method for producing polyacetal resin composition
JP2011132370A